Kepemimpinan Dalam Pendidikan Islam - Rahman Afandi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Leadership plays a very important role on the direction, goals, and the success level in reaching the goals that have been set. Education is one form of organization where success is largely determined by the level of management and leadership factors. This fact shows just how big a role of leadership in education. Therefore, improvement of management systems and leadership in education is a compuilsory. Keywords : leadership, education, contribution.